2020
DOI: 10.1101/2020.10.09.20210039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EVALUATION OF ELEVEN IMMUNOCHROMATOGRAPHIC ASSAYS FOR SARS-CoV-2 DETECTION: INVESTIGATING DENGUE CROSS-REACTION

Abstract: Background: COVID-19 disease (Coronavirus disease 2019) caused by SARS-CoV-2 (Severe acute respiratory syndrome coronavirus 2) is widespread worldwide, affecting more than 11 million people globally (July 6th, 2020). Diagnostic techniques have been studied in order to contain the pandemic. Immunochromatographic (IC) assays are feasible and low cost alternative for monitoring the spread of COVID-19 in the population. Methods: Here we evaluate the sensitivity and specificity of eleven different immunochromatogr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(26 reference statements)
0
5
0
1
Order By: Relevance
“…The assumption of cross-reaction between SARS-CoV-2 and DENV was reported in several studies. However, most of these studies have built this assumption based on the antigenic cross-reactivity using the LFA and a few based on ELISA results detecting NS1 antigens [ 9 , 10 , 11 , 12 ]. Therefore, we investigated the possible serological cross-reaction between SARS-CoV-2 and DENV using more advanced serological assays, which are the CL-900i automated analyzer and the ELISA test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption of cross-reaction between SARS-CoV-2 and DENV was reported in several studies. However, most of these studies have built this assumption based on the antigenic cross-reactivity using the LFA and a few based on ELISA results detecting NS1 antigens [ 9 , 10 , 11 , 12 ]. Therefore, we investigated the possible serological cross-reaction between SARS-CoV-2 and DENV using more advanced serological assays, which are the CL-900i automated analyzer and the ELISA test.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have reported serological cross-reactivity of the immune responses between SARS-CoV-2 and DENV [ 2 , 9 ]. Most of the available studies are based on point-of-care rapid testing kits [ 11 , 12 , 13 , 14 ]. However, some rapid test kits have low specificity and can generate false positives [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A evidência da coinfecção entre Dengue e COVID-19 foi apresentada nos estudos, com ocorrência de 38,4% a 44,6% dos casos de pessoas que contraíram a COVID-19 e desenvolveram a Dengue ou vice versa (14) . Referente à idade dos participantes foram: jovens 18 a 26 anos (16,20,24,26) , adultos jovens de 31 a 37 anos (15,17,21,(24)(25) , adultos de 41 a 57 anos (14,15,(23)(24)(25) , além de idosos de 60 a 80 anos (20,22,27,35) . A Covid-19 simulou resultados falso positivos de Dengue (23) em decorrência da janela sorológica e do processo de soro conversão, o que dificultou o diagnóstico clínico e o tratamento efetivo.…”
Section: Resultadounclassified
“…There has been reported cases of cross-reaction between SARS-CoV-2 and DENV and available studies have analysed this relationship mostly on rapid tests and a few on ELISA (6-9). A study analysed 55 SARS-CoV-2 positive samples on lateral flow rapid test and ELISA for dengue specifics antibodies and 95 dengue positive pre-pandemic samples on ELISA for S protein of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…There is a limited number of studies analysing the serological cross-reactivity between SARS-CoV-2 and DENV, most of the available studies are based on the POC rapid testing kits (6-9). However, some rapid test kits have low specificity and can generate false positives (10).…”
Section: Introductionmentioning
confidence: 99%